ANATOMICAL AND FUNCTIONAL OUTCOME FOLLOWING TYPE-1 TYMPANOPLASTY IN CHRONIC TUBOTYMPANIC SUPPURATIVE OTITIS MEDIA: TypeI Tympanoplasty - Umar, Adnan Saleem; Ahmed, Zubair (Pakistan Armed Forces Medical Journal, 2008)
Objectives: To assess the improvement in hearing and rate of graft uptake after type-1 tympanoplasty in chronic tubotympanic suppurative otitis media and to identify the complications of surgery.Study Design: Interventional study (quasi experimental).Place and Duration: Department of Ear Nose Throat (ENT) and department of Head & Neck surgery at Combined Military Hospital (CMH) Rawalpindi from July 2002 to Feb 2004.Materials and Methods: A total of 107 cases of chronic suppurative otitis media tubotympanic type with dry central tympanic membrane (TM) perforations were selected. Out of these, 85 cases were available for follow-up. The patients were evaluated by history, clinical examination and by examination under otomicroscope. All other cases with ear discharge and cholesteatomas were excluded. Preoperative and postoperative audiograms were done, laboratory investigations and X-ray of mastoids were also carried out. All the patient underwent type-I tympanoplasty, using temporalis fascia with underlay technique. The postoperative results were evaluated with respect to anatomical and functional out come.  Results: Our study showed an overall success rate of 92.95% as far as the graft uptake was concerned. Out of 85 cases, on examination at the interval of three months the perforations was closed in 79 (92.94%) cases. Improvement in hearing was seen in 73 (85.88%) cases, with notable reduction in air-bone gap at the end of three months. The complications at the interval of three months were dislodgement of graft 1 (1.17%) case, residual perforation 5 (5.88%) cases, deterioration of hearing 1 (1.17%) case, small retraction pockets 3 (3.52%) cases and metallic taste in mouth 2 (2.35%) cases.Conclusion: From this study we concluded that in dry ears with central perforations, type-I tympanoplasty using temporalis fascia with underlay technique is a very satisfactory and reliable procedure for closing the tympanic membrane perforations and to restore hearing, provided attention is paid to aseptic technique, anatomical landmarks and by exercising good clinical judgment.